Crise financeira, recessão e risco de depressão no capitalismo globalizado do século XXI: impactos nos EUA, zona do euro e Brasil - CARVALHO, David Ferreira (Associação Keynesiana Brasileira, 2022)
The Great Depression of the 1930s is considered until today as the most serious disease of the economic which endangered the existence of modem capitalism. Until now, economists investigate the causes of this terrible pandemic. Hyman Minsky, following the trail of John Maynard Keynes, developed theories of financial fragility and instability that explain the causes of financial crisis in contemporary capitalism. The large current global recession has its origin in the subprime crisis that occurred in 2.008 in the U.S. and spread to the rest of the world. The purpose of this paper is to investigate the causes and effects of the crisis of contemporary capitalism that has as its epicenter in the USA and then spread to the EuroZone and the rest of the world, including Brazil, with the risk of another Great Depression at the beginning of the XXI Century.